DNA Mini-Barcodes as A Molecular Marker for Various Hairtail Fish Products Traceability - Asadatun Abdullah; Mala Nurilmala; Kinanti Permata Sitaresmi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Hairtail fishery is an important fishery commodity with high economic value as export commodity. Authentication based on DNA mini-barcodes can be applied to overcome seafood fraud and to support Indonesian traceability system. This study was aimed to design species-specific primers of DNA minibarcodes and authentication of various processed hairtail fish products such as smoked, baked, fried, canned, and boiled. Analytical method applied PCR-based of cytochrome c oxidase 1 (COI) full length andmini-barcodes. Mini-barcode primer specific for hairtail (Trichiurus lepturus) successfully amplified DNA of processed hairtail fish. The BLAST analysis showed the samples were identified as Trichiurus sp. and T. lepturus with homology level of 91% to 100%. Phylogenetic analysis showed the processed sample (LC dan LD) were in the same group with T. lepturus.